ALIH WAHANA TUTURAN TOKOH PADA KARYA BERJUDUL YOU AND INSECURITIES DALAM ALTERNATIVE UNIVERSE (AU) KE NOVEL SERTA IMPLIKASINYA PADA PEMBELAJARAN BAHASA INDONESIA DI SMA. - Rahma Bidari Tuankotta; Trie Utari Dewi (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2026)
This research aims to describe the adaptation of the character's speech act of Alternative Universe (AU) entitled You and Insecurities to a novel in relation to Indonesian language learning in high school. The method used is descriptive qualitative with a pragmatic approach. The data for this research are dialogues or speech of characters in AU and the novel entitled You and Insecurities as the research source. The results of this research are the forms of reduction, addition, and varied changes with the types of declarative, assertive, expressive, directive, and commissive speech. This study has implications for high school literature learning in the material of writing drama scripts based on short stories through KD 3.8, 3.9, and 4.19.